Senior Care and Robotic Assistance - Lakshay Garg (International Journal of Advanced Science and Technology, 2020)
India’s elder population continue to grow at an unmatched rate. Presently, the people aged 65 and over make up to 8.5 percent of people worldwide (617 million). A number of people are facing problems in doingg their daily chores and caretakers or assistants may not be able to match the speed of increase in requirement for assistance. Older people who want to live independently at home have no one to help them at home. Robots do have the capability to help elder people living independently at home in cities. Moreover, the research is aimed to recognize the areas of need of the older people, and the solutions that are available. In particular, various robotic solutions are studied and analysed and then the areas for future study are identified. There is very little known about the robot assistance at home. 15-20 of Indian Older Generation people were asked what they want the robot want to do for them. In a group, they answered with various tasks they wanted the robots perform for them. This information, alongside their survey reactions, recommend that the elder population was commonly open to robot help however were separating in their acknowledgment of help for various undertakings. Older people found that robot assistance was far better than human assistance since they found out that robots were 24X7 available for them which a human can’t accomplish. This research aims to gain insights about what the older population think of robotic help and assistance over human help and assistance. This research also aims at understanding whether the senior population will prefer robots in this upcoming technological advancement world.